The centrality of Sufism in understanding the Bahaia religion - Damad, Saadoon Mohsin; Sachjt, Khalid Hantoosh (Al-Adab Journal, 2021)
This research deals with the Baha’i religion, in an attempt to overcome the misunderstanding surrounding it, whereby the believers were treated as a group trying to destroy the Islamic religion, and the claim of Bahaullah as the Messenger of this time was also met, as well as his claim that he was the last transfiguration of God was accepted as a form of heresy and deviation from The den. Which required that a campaign of skepticism and accusation was launched that did not end until now, as religion was accused of being driven by international intelligence, or that it was a branch of Freemasonry. Until now, this religion has not been widely recognized. The process of deciphering the ambiguity carried out by this research is based on using the Sufi root in it to provide a clear explanation of everything that is raised around it, which is believed to be contrary to Islam or used to destroy it and expose its beliefs to deliberate distortions. It is well known that Sufism is based on presenting two understandings of religion, and indeed of life in general, both outward and mystical, and the esoteric understanding is based on a process of interpretation of almost everything and dealing with life and people as manifestations of the revelation of God, and the journey of mysticism is based on several levels, it comes in Its end is the order of union with the truth, whereby the Sufi speaks her name or expresses her will. Accordingly, it is not surprising that Hussain is based on the Mazandaran, who according to this research is a Sufi in the Shaykh-Shiite way, presenting himself as a manifestation of the revelation of God, just as the faith of the believers in his claim is no longer surprising if we present them as Sufi, and it has often been issued by the sheikhs of Sufism in history The Islamic claims are similar.